2017
DOI: 10.3389/fphys.2017.00856
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term High- and Moderate-Intensity Training Modifies Inflammatory and Metabolic Factors in Response to Acute Exercise

Abstract: Purpose: To compare the acute and chronic effects of high intensity intermittent training (HIIT) and steady state training (SST) on the metabolic profile and inflammatory response in physically active men.Methods: Thirty recreationally active men were randomly allocated to a control group (n = 10), HIIT group (n = 10), or SST group (n = 10). For 5 weeks, three times per week, subjects performed HIIT (5 km 1-min at 100% of maximal aerobic speed interspersed by 1-min passive recovery) or SST (5 km at 70% of maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
2
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 36 publications
1
40
2
3
Order By: Relevance
“…After 4 weeks of training, an acute elevation in anti‐inflammatory cytokines, but not in proinflammatory mediators, occurred at the end of the 8th session of HIIE. Interestingly, the acute enhancement of IL‐10 and IL‐1ra after HIIE was not observed by others authors, who found no impact on the elevation of proinflammatory and anti‐inflammatory cytokines in lean physically active males . The discrepancies between our results and past studies may be related to differences in HIIT progression over the weeks and the population studied.…”
Section: Discussioncontrasting
confidence: 99%
“…After 4 weeks of training, an acute elevation in anti‐inflammatory cytokines, but not in proinflammatory mediators, occurred at the end of the 8th session of HIIE. Interestingly, the acute enhancement of IL‐10 and IL‐1ra after HIIE was not observed by others authors, who found no impact on the elevation of proinflammatory and anti‐inflammatory cytokines in lean physically active males . The discrepancies between our results and past studies may be related to differences in HIIT progression over the weeks and the population studied.…”
Section: Discussioncontrasting
confidence: 99%
“…However, lowintensity exercise failed to inhibit the increase in serum inflammatory cytokine level in the present study. It is important to set optimal exercise intensity for decreasing the systemic expression level of inflammatory cytokines (39). It has been suggested that moderate or high-intensity exercise is required to decrease the expression level of inflammatory cytokines (39).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to set optimal exercise intensity for decreasing the systemic expression level of inflammatory cytokines (39). It has been suggested that moderate or high-intensity exercise is required to decrease the expression level of inflammatory cytokines (39). Therefore, low-intensity exercise was not enough to decrease the systemic expression level of inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…또한 사람을 대상으로 한 연구에서는 근세포내 지질축 적 정도가 운동 트레이닝에 의해 변화된다는 결과가 있었다 [9]. 최근에 는 대사와 염증관련 적응의 측면에서 서로 다른 강도의 장단기 운동 이 혈중 IL-5, IL-10, TNF-alpha, IL-6/IL-10, NEFA, 글루코스 등의 수준 에 긍정적인 영향을 끼친다는 연구와 같이 [10] Biosynthesis of other secondary metabolites 범주에서는 neomycin, ka-…”
Section: 서 론unclassified